Variation in Event-Related Potentials by State Transitions - Higashi, Hiroshi; Minami, Tetsuto; Nakauchi, Shigeki (Frontiers in Human Neuroscience, 2017)
The probability of an event's occurrence affects event-related potentials (ERPs) on electroencephalograms. The relation between probability and potentials has been discussed by using a quantity called the surprise that represents the self-information that humans receive from the event. Previous studies have estimated the surprise based on the probability distribution in a stationary state. Our hypothesis is that state transitions also play an important role in the estimation of the surprise. In this study, we compare the effects of the surprise on the ERPs based on two models that generate an event sequence: a model of a stationary state and a model with state transitions. To compare these effects, we generate the event sequences with Markov chains in order to avoid the convergence of the state transition probability with the stationary probability. Our trial-by-trial model-based analysis showed that the stationary probability better explains the P3b component and the state transition probability better explains the P3a component. The effect on P3a suggests that the internal model, which is constantly and automatically generated by the human brain to estimate the probability distribution of the events, approximates the model with state transitions because the Bayesian surprise, which represents the degree of updating of the internal model, is highly reflected in P3a. The global effect reflected in P3b, however, may not be related to the internal model because P3b depends on the stationary probability distribution. The results suggest that an internal model can represent state transitions and the global effect is generated by a different mechanism than the one for forming the internal model.